A comparative analysis of the laws governing phishing in internet banking / Mohamad Shafiq Mohd Sazalli, Muhammad Fahmi A Jamil and Nur Afiqah Hambali - Mohd Sazalli, Mohamad Shafiq; A Jamil, Muhammad Fahmi; Hambali, Nur Afiqah (2012)
The study is mainly focused on the laws governing in Internet banking. Adopting a doctrinal approach, this research reveals that there are many weaknesses found in the current legal framework in Malaysia. This research has suggested several recommendations in order to improve the current laws governing phishing. This study has also made a comparison with the laws in the United Kingdom, the United States of America, Singapore, Thailand and Australia.